2016
DOI: 10.1080/21658005.2016.1182822
|View full text |Cite
|
Sign up to set email alerts
|

Immunological conception of African swine fever

Abstract: This article surveys findings of the long-term investigations into the virology and immunology of African swine fever (ASF) conducted at the All-Russian Research Institute for Veterinary Virology and Microbiology under the scientific supervision of the authors. Based on the scientific data obtained, 14 postulates of the ASF immunological conception were formulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…Eight ASFV serogroups (SG) were defined and thoroughly characterized; however, more SG may exist. Additional parameters such as HA density (number of erythrocytes per infected cells) and erythrocyte contact maps were used to refine ASFV isolate classification (Makarov et al, 2016;Sereda et al, 1994). The HAI based assay was used for ASFV strains selection and screening for development a potential liveattenuated vaccine candidates (Sereda et al, 1992;Sereda and Balyshev, 2011).…”
Section: Antigenic Diversity Serogroupsmentioning
confidence: 99%
“…Eight ASFV serogroups (SG) were defined and thoroughly characterized; however, more SG may exist. Additional parameters such as HA density (number of erythrocytes per infected cells) and erythrocyte contact maps were used to refine ASFV isolate classification (Makarov et al, 2016;Sereda et al, 1994). The HAI based assay was used for ASFV strains selection and screening for development a potential liveattenuated vaccine candidates (Sereda et al, 1992;Sereda and Balyshev, 2011).…”
Section: Antigenic Diversity Serogroupsmentioning
confidence: 99%
“…Later, it was confirmed that due to the high probability of reversion and poor immunobiological characteristics of many attenuated strains the live vaccines based on them were unsuitable for widespread use [9]. The experiments to develop inactivated or subunit vaccines against ASF using conventional methods have also failed because of their inability to induce cell-mediated immunity, which plays a crucial role in the formation of protection at ASF [10][11][12]. However, the research on the development of safe protective candidate drugs for the temporary protection of swine, ensuring their protection in enzootic areas or the planned slaughter on large pig farms, is ongoing [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that cytotoxic Т-lymphocytes (CTL) are important for maintenance of virus-specific protection in the early period following ASFV infection [19,20]. Cytolysis percentage of macrophages infected by homologous isolate was higher than that for heterologous isolates, which evidenced on immunotype specificity of CTL [21].…”
mentioning
confidence: 99%
“…Therefore, immune protection against ASFV is likely due to effect of killer T-lymphocytes and ADCC against viral proteins at surface of infected monocytes (macrophages) [20,23]. Synergy of CTLs and antibodies in ADCC had been proved by in vitro tests with the use of homological cultures of leukocyte cells obtained before and on day 6 post injection of high dose of the attenuated ASFV strain.…”
mentioning
confidence: 99%